Review of Passenger Safety Equipment on KMP. Kormomolin at Bira – Pamatata Tracking, South Celebes Province - Siti Nursyakirah Binti Yuslan; Alexander Hilmi Perdana; Shinta Aulia Triany (IWJ : Inland Waterways Journal, 2019)
Ship accident in mid-2018 and On Bira - Pamatata tracking cause casualties 35 people were killed, 155 people survived, and the other one has not been found. Existence of a helper tool safety becomes a critical component to creating a safe and secure shipping. On the other hand, the Safety Of Life At Sea (SOLAS) 1974 2014 Amendments to the 2014 Amendment has set safety standards Sailing. The research was conducted by collecting data related to the safety equipment on KMP. Kormomolin includes the number and condition of lifejacket, lifebuoy, liferaft and lifeboat. The analysis was done by comparing the requirements contained in the Safety Of Life At Sea (SOLAS) 1974 2014 Amendments to the 2014 Amendment on the safety of shipping equipment to existing conditions in the field. Based on the analysis, it can be concluded that the number of passenger safety tools contained in KMP. Kormomolin on cross-Bira - Pamatata still incomplete when compared with the number of penumpan and crew as well as the condition of some of the safety equipment in bad condition so we need counseling, supervision, enforcement, and the improvement of the means of occupant safety in accordance with the standards of the Safety Of Life at Sea (SOLAS) 1974 Amendment 2014 to the creation of security and comfort for the user services and operator of the ship.